Hijab dalam Pandangan Muslimah - Ken Ayu Kartikaningrum (MAGHZA, 2019)
This article discusses the hijab in the view of the Muslim community Caring for the Hijab Purwokerto. This research is a type of field research. In analyzing data, the instruments that researchers use are in-depth interviews, observations, and data that researchers get from journals, books, and newspapers. Researchers, in this case, use the Social Construction Theory from Peter L Berger's theory. This theory is more focused on the meaning and joint interpretation constructed in community networks. From the research conducted, the researchers focused on two main things, namely: (1) The view of the Muslim community caring for Hijab Purwokerto on the hijab. (2) Genealogy of Muslim Hijab Care for Hijab Purwokerto community understanding hijab